Temporal Information Processing and its Relation to Executive Functions in Elderly Individuals - Nowak, Kamila; Dacewicz, Anna; Broczek, Katarzyna; Kupisz-Urbanska, Malgorzata; Galkowski, Tadeusz; Szelag, Elzbieta (Frontiers in Psychology, 2016)
Normal aging triggers deterioration in cognitive functions. Evidence has shown that these age-related changes concern also executive functions (EF) as well as temporal information processing (TIP) in a millisecond range. A considerable amount of literature data has indicated that each of these two functions sets a frame for our mental activity and may be considered in terms of embodied cognition due to advanced age. The present study addresses the question whether in elderly subjects the efficiency of TIP is related to individual differences in EF. The study involved 53 normal healthy participants aged from 65 to 78. In these subjects TIP was assessed by sequencing abilities measured with temporal-order threshold (TOT). It is defined as the minimum time gap separating two auditory stimuli presented in rapid succession which is necessary for a subject to report correctly their temporal order, thus the relation ‘before-after’. The EF were assessed with regard to the efficiency of the executive planning measured with the Tower of London-Drexel University (TOLDX) which has become a well-known EF task. Using Spearman’s rank correlations we observed two main results. Firstly, the indices of the TOLDX indicated a coherent construct reflecting the effectiveness of executive planning in the elderly. Initiation time seemed dissociated from these coherent indices, which suggested a specific strategy of mental planning in the elderly based on on-line planning rather than on preplanning. Secondly, TOT was significantly correlated with the indices of TOLDX. Although some of these correlations were modified by subject’s age, the correlation between TOT and the main index of TOLDX (‘Total Move Score’) was rather age resistant. These results suggest that normal aging may be characterized by an overlapping of deteriorated TIP and deteriorated EF.